The Relationship between Synchronous and Asynchronous Learning and Self-Directed Learning in the Remote Teaching Environment - Karawani, Muslima; Preece, Abdul Shakour (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
With the advent of the COVID pandemic, teaching and learning moved online and synchronous and asynchronous modes of education became more commonplace. Yet, in such a scenario, the role played by learners becomes even more vital, since they need to become more dependent on themselves as they adapt to the online learning. In the light of this, the study aimed to explore the relationships between synchronous and asynchronous learning and SDL that became more prevalent during and after the pandemic. The study used a quantitative research methodology that included de-scriptive quantitative statistics, comprising a 39-item survey. The statistical assumptions for all variables were examined by means of applying four competing struc-tural equation models (SEM) to explain associations between remote teaching and learning (“RTL”) and SDL (“SDL”) and also to find one model that best explained these relationships. A parametric correlation (Pearson's correlation coefficient) was used to examine statistical relationships between variables. The study’s findings reveal a significant relationship between the independent variables of synchronous and asynchronous learning methods and the dependent variables related to students SDL skills, i.e., self-management, self-monitoring and motivation. etc. In the light of this, the researchers rec-ommend that students continue studying online for some of their key courses, even after returning to normal, to improve their SDL skills.